Prevalence Of Average Blood Pressure Levels In The Unmarried Men's Population Of Andizhan City - U.Q.Ahmadalieva (Genius Journals, 2025)
This study focuses on determining the average blood pressure levels and their distribution among the male population in Andijan city who are not formally employed (informal sector). The research analyzes the frequency of hypertension and hypotension cases, their distribution across different age groups, and their correlation with sociodemographic factors. The results obtained are of significant importance for developing preventive measures in the field of public health
Keywords: Andijan city; informal population; male population